Molecular characterization of Hb hamilton hill (HBA2: c.388delC), a novel HBA2 variant generating a premature termination codon and truncated HBA2 chain - Qadah, T.; Finlayson, J.; North, E.; Ghassemifar, Reza (Informa Healthcare, 2015)
In recent years, the identification of a-thalassemias caused by nondeletional mutations has increased significantly due to the advancement of sensitive molecular genetics tools. We report clinical and experimental data for a novel frameshift mutation caused by a single base deletion at position 388 in exon 3 of the a2-globin gene (HBA2: c.388delC; Hb Hamilton Hill), resulting in the phenotype of a-thalassemia (a-thal). Hb Hamilton Hill was identified in an adult female of unknown ethnicity investigated for unexplained microcytosis. Direct DNA sequencing of the HBA2 gene revealed a heterozygous mutation, HBA2: c.388delC, and the molecular effect of this mutation was assessed experimentally using our previously described in vitro model. The experimental analysis involved transfection of a human bladder carcinoma (5637) cell line with expression vectors carrying either HBA2-wild type (HBA2-WT) or HBA2: c.388delC followed by total RNA purification and cDNA synthesis. Both wild type and mutant gene expression was studied and compared at the transcriptional and translational levels using quantitative real time polymerase chain reaction (qReTi-PCR) and immunofluorochemistry (IFC), respectively. Our experimental data showed a significant reduction by 25.0% (p=0.04) in the transcriptional activity generated from HBA2: c.388delC compared to HBA2-WT. As a result of this base deletion, a frameshift in the open reading frame generates a premature termination codon (PTC) at codon 132 of exon 3 resulting in the formation of a truncated a-globin chain. The truncated a-globin chain, observed by the IFC technique, is most likely unstable and undergoes a rapid turnover resulting in the thalassemic phenotype.